Pengaruh Model Pembelajaran Group Investigation terhadap Hasil Belajar Siswa pada Konsep Momentum dan Impus - Danu Jadmiko; Darsikin Darsikin; Marungkil Pasaribu (Jurnal Kreatif Online, 2021)
The study aimed to determine the effect of using the Group Investigation learning model on student learning outcomes on the concepts of momentum and impulse. This type of research was a quasi-experimental design with the non-equivalent pretest-posttest design. The population of this study was all students of class X IPA SMA Negeri 4 Palu. The sampling technique used in this research was purposive sampling. The sample of this study was class X IPA 6 (n=35) as the experimental group and class X IPA 4 (n=35) as the control group. The instrument was a test of learning outcomes in the form of multiple-choice questions. The learning outcomes test obtained showed that the average score of the experimental group was 15.16 with a standard deviation of 3.23 and the average score of the control group was 10.56 with a standard deviation of 3.08. Based on the results of hypothesis testing obtained tcount = 5.48 and t0.0975(68) = 1.99 at a significance level of = 0.05. This result means that the tcount is outside the H0 reception area. So, it can be concluded that there is an effect of using the Group Investigation learning model on student learning outcomes on the concepts of momentum and impulse.